Neutrophil extracellular traps mediate the crosstalk between glioma progression and the tumor microenvironment via the HMGB1/RAGE/IL-8 axis - Zha, Caijun (Cancer Biol Med, 2020)
Objective: Neutrophil extracellular traps (NETs) produced by tumor-infiltrating neutrophils (TINs) are associated with poor prognosis in patients with several types of cancer. However, the mechanisms underlying the involvement of NETs in glioma progression remain largely unknown. This study aimed to elucidate the roles of NETs in biological processes that drive the crosstalk between glioma progression and the tumor microenvironment. Methods: Neutrophil infiltration and NETs formation were investigated in glioma tissue through immunohistochemistry, and their relationships with clinicopathological features and outcomes were statistically evaluated. The effects of NETs on glioma cell progression were studied in a co-culture system. In vivo and in vitro experiments validated the reactive oxygen species activity and cytokine production of TINs, as well as the ERK signaling pathway activation and the metastasis of gliomas. Results: Neutrophil infiltration and NETs formation were induced in high-grade glioma compared with low-grade glioma. NETs induced by TINs were determined to be an oncogenic marker of high-grade gliomas and to be involved in cell proliferation and invasion. NETs overproduction promoted glioma cell proliferation, migration, and invasion. Furthermore, HMGB1 was found to bind to RAGE and activate the NF-κB signaling pathway in vitro. In addition, NETs stimulated the NF-κB signaling pathway, thus promoting IL-8 secretion in glioblastoma. Subsequently, IL-8 recruited neutrophils which in turn mediated NETs formation via the PI3K/AKT/ROS axis in TINs. Conclusions: Our results suggest that NETs produced by TINs mediate the crosstalk between glioma progression and the tumor microenvironment by regulating the HMGB1/RAGE/IL-8 axis. Targeting NETs formation or IL-8 secretion may be an effective approach to inhibit glioma progression.